AL-QALB, AL-FU'AD, AL-'AQL AND AL-NASIYAH IN THE QUR'AN (Exploring Meaning in Spiritual and Neurological Contexts) - Jabbar, Luqman Abdul (The Pontianak State Institute of Islamic Studies, 2024)
This article explores the spiritual and neurological concepts related to the terms al-qalb, al-fu’ad, al-‘aql, and al-nasiyah in the Qur'an and modern science. Al-qalb and al-fu’ad refer to centers of feeling and intuition in Islamic tradition, where al-qalb is often associated with the spiritual and emotional core of a person, while al-fu’ad focuses more on inner aspects and depth of understanding. The concept of al-‘aql pertains to intellect or reason, encompassing the ability to discern, comprehend, and make wise decisions. Al-nasiyah, on the other hand, refers to the prefrontal cortex of the brain, which is responsible for behavioral control and decision-making. By comparing the meanings of these terms in the Qur'anic context with contemporary scientific findings, this article aims to demonstrate the alignment between spiritual perspectives and neurological knowledge regarding the functions and impacts of various centers of thought and feeling in humans. This analysis reveals how the metaphorical and literal meanings of these terms complement each other in a holistic understanding of the human soul and mind.